2006
DOI: 10.1590/s0102-695x2006000400019
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the content of tannins in barks of barbatimão species

Abstract: RESUMO: "Variação sazonal dos teores de taninos em cascas de espécies de barbatimão". A composição de taninos em cascas de espécies de barbatimão, Stryphnodendron adstringens (Mart.) Cov. and S. polyphyllum (Mart.), foi analisada mensalmente durante um ano. Os resultados foram correlacionados com as condições climáticas do período de coleta (precipitação, umidade e temperatura média) através de métodos quimiométricos. Análise de componentes principais dos dados mostrou uma tendência de maior produção de tanino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 18 publications
3
12
1
5
Order By: Relevance
“…In contrast to previous studies (Scogings et al, 2004;Santos et al, 2006;Fang et al, 2011) the levels of all phenolics did not present any correlation with climatic changes, such as rainfall and temperature. Clusters I and IV have no significant differences in all phenol levels despite occurring in distinct seasons (Table 1).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies (Scogings et al, 2004;Santos et al, 2006;Fang et al, 2011) the levels of all phenolics did not present any correlation with climatic changes, such as rainfall and temperature. Clusters I and IV have no significant differences in all phenol levels despite occurring in distinct seasons (Table 1).…”
Section: Resultscontrasting
confidence: 99%
“…Tannin and terpenoid amounts alter during the development of the plant and also as a response to environmental changes (Salminen et al, 2001;Salminen et al, 2004;Scogings et al, 2004;Santos et al, 2006;Solar et al, 2006;Fang et al, 2011). Previous studies showed the seasonal influence on the terpenoids composition of the E. uniflora leaves oil (Costa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Resultados semelhantes foram encontrados por Silva et al (7) , que confirmaram a presença de saponinas, catequinas, taninos, fenóis e antraquinonas, mas constataram ausência de alcalóides e esteróides/triterpenóides. Silva et al (13) , em estudos fitoquímicos por espectrometria de massa e espectroscopia de ressonância magnética nuclear, revelaram que as catequinas são um componente importante na classe dos taninos condensáveis. Os ensaios da atividade antibacteriana in vitro dos extratos (ECH, EA, EE) da casca de Abarema cochliacarpos mostraram inibição contra a bactéria Gram-positiva Staphylococcus intermedius em todas as concentrações testadas (100, 50, 25, 12,5 e 6,25 mg/mL), exceto para o extrato em ciclohexano, que não demonstrou inibição nas concentrações de 12,5 e 6,25 mg/mL.…”
Section: Resultado E Discussãounclassified
“…The latter has very similar flavonoid content but twice more polyphenol concentration compared to C. sylvestris (0.640 g% and 2.22 g% for flavonoids and polyphenols, respectively); these parameters were measured by the methodology described elsewhere (39). This variation in plant compounds can change medicinal properties (40). Parameters such as ash production, humidity, flavonoids and phenols are important for phytochemical characterization and maintenance of a physicochemical standard of plant extracts.…”
Section: Resultsmentioning
confidence: 99%